2018
DOI: 10.3390/md16050162
|View full text |Cite
|
Sign up to set email alerts
|

Ascidian Toxins with Potential for Drug Development

Abstract: Ascidians (tunicates) are invertebrate chordates, and prolific producers of a wide variety of biologically active secondary metabolites from cyclic peptides to aromatic alkaloids. Several of these compounds have properties which make them candidates for potential new drugs to treat diseases such as cancer. Many of these natural products are not produced by the ascidians themselves, rather by their associated symbionts. This review will focus mainly on the mechanism of action of important classes of cytotoxic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 193 publications
(242 reference statements)
0
26
0
6
Order By: Relevance
“…Notably, in the MCF-7 cell line, which was sensitized to irinotecan by GA-13315, the changes in mRNA expression levels were uncoupled with that of the protein expression levels for Top1, Chk1 and Bax. This imbalance between gene and protein expression levels may be caused by the potential effects of GA-13315 on the mRNA (half-life) stability (41)(42)(43). This phenomenon was not observed in HCT116 cells, thus the sensitizing effect of GA-13315 was probably associated with the disruption of the protein translation process; however, this hypothesis requires further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…Notably, in the MCF-7 cell line, which was sensitized to irinotecan by GA-13315, the changes in mRNA expression levels were uncoupled with that of the protein expression levels for Top1, Chk1 and Bax. This imbalance between gene and protein expression levels may be caused by the potential effects of GA-13315 on the mRNA (half-life) stability (41)(42)(43). This phenomenon was not observed in HCT116 cells, thus the sensitizing effect of GA-13315 was probably associated with the disruption of the protein translation process; however, this hypothesis requires further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…Polyketide synthetases are large multienzyme machineries. Natural products having polyketide and non-ribosomal peptide (NRP) structures are generally found to be of microbial origin [13]. Polyketides and the synthetic analogs have been discovered as important lead compounds with various activities, such as blocking protein tyrosine phosphatase and inhibiting the ATP synthase complex [73].…”
Section: Polyketides From Ascidiansmentioning
confidence: 99%
“…However, the genetic basis driving ascidians to contribute and adapt marine ecosystem remains to be elusive. It has been reported that metabolic products in ascidians, such as alkaloids, cyclic peptides, and polyketides, could demonstrate high defensive bioactivity that may facilitate host ecological success in environmental invasion and adaptation [8][9][10]. These bioactive compounds could be synthesized by ascidians or their bacterial symbionts [11,12].…”
Section: Introductionmentioning
confidence: 99%